Pemasaran Digital di Era Pandemi Covid-19 - Genesis Sembiring Depari; Alfonsius; Elisabet Tambunan; Roberto Purba (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The COVID-19 pandemic has brought many changes in human life. Life processes that were previously done manually are now leading to the massive use of digital technology. This opens up a myriad of new opportunities to reach potential customers, serve existing customers and in some cases increase the efficiency of business operations. Thus, the ability to use digital technology to improve business efficiency is increasingly undeniable. Therefore, the team of lecturers from the Management Study Program of UPH Medan and Sari Mutiara University initiated to conduct training on the use of digital marketing technology in the era of the COVID-19 pandemic. In this training activity, 12 steps of digital marketing were explained and could be directly applied by participants consisting of students of the Management study program of UPH Medan, USMI Management study program and the general public.